2021
DOI: 10.22271/tpi.2021.v10.i12p.9503
|View full text |Cite
|
Sign up to set email alerts
|

Agro-meteorological indices, phenological stages and productivity of durum wheat (Triticum durum Desf.) influenced by seed soaking and foliar spray of stress mitigating bio-regulators under conserved moisture condition

Abstract: during the rabi seasons of the years 2017-18 and 2018-19 to determine the response of meteorological indices on seed soaking and foliar sprays of stress mitigating bio-regulators under conserved soil moisture conditions in durum wheat. The experiment comprised of four treatments of seed soaking viz; No seed soaking (S0), Seed soaking with water (S1), Seed soaking with 100 ppm Salicylic acid (S2) and Seed soaking with 500 ppm Thiourea (S3) and four treatments of foliar spray viz; No spray(C0), Water spray (C1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Asthir et al, (2016) [3] reported that the thiourea application on wheat ameliorated the heat-induced damages by stimulating the total antioxidant activity through decrease in lipid peroxidation and membrane injury. Foliar spray of thiourea (C 3 ) @ 1000 ppm provide more opportunity time to the crop for its photosynthetic activities and translocation of photosynthates from source to sink which might be subsequently converted to higher yield of durum wheat (Choudhary et al, 2021) [12] ~ 714 ~ [19] . Proline also represents a lipid peroxidation inhibitor (Jain et al, 2001) [6] .…”
Section: Moisture Content (%)mentioning
confidence: 99%
“…Asthir et al, (2016) [3] reported that the thiourea application on wheat ameliorated the heat-induced damages by stimulating the total antioxidant activity through decrease in lipid peroxidation and membrane injury. Foliar spray of thiourea (C 3 ) @ 1000 ppm provide more opportunity time to the crop for its photosynthetic activities and translocation of photosynthates from source to sink which might be subsequently converted to higher yield of durum wheat (Choudhary et al, 2021) [12] ~ 714 ~ [19] . Proline also represents a lipid peroxidation inhibitor (Jain et al, 2001) [6] .…”
Section: Moisture Content (%)mentioning
confidence: 99%